Gambaran Perilaku Jajan Siswa/Siswi Kelas 6 dan Kelas 9 di Sekolah Penuai Cibubur Jatisampurna Bekasi - Elmina Tampubolon (Elisabeth Health Jurnal, 2021)
Background: School children are food consumers who have been active and independent in determining the food they want, both snacks at school and elsewhere. Based on the initial survey, during recess almost all students eat snacks in the canteen and the snacks chosen are mostly fried or boiled instant noodles. This of course can have an impact on the health of students. The purpose of the study was to obtain an overview of the snacking behavior of students in grade 6 and grade 9 at the Cibubur Harvest School.Methods: The research design used is a case study. The sample/informant consisted of four 6th grade elementary school students and 4 9th graders. While the key informant was 1 canteen owner. The data collection method used is semi-structured in-depth interviews and observation. The data was processed and tested for validity by using triangulation, then data analysis was carried out in the form of content analysis.Results: The results showed that students' snacking behavior was influenced by knowledge, attitudes, canteen availability, pocket money, access to information, support from friends, teachers and parents. The results of observations showed that the types of snacks chosen by grade 9 students were more varied and nutritionally balanced compared to grade 6 students.Conclusion: For parents, it is necessary to always direct their children to choose healthy snacks and limit the amount of pocket money for students because it can encourage students to snack more often.